(untitled) (UNWE Yearbook, 2024)
Nuclear energy and renewable energy are two prominent sources of power that have been under scrutiny for their environmental impact and sustainability. Nuclear energy, derived from splitting atoms to generate heat, produces large amounts of energy with minimal greenhouse gas emissions. However, it poses risks such as radioactive waste and potential accidents. On the other hand, renewable energy sources like solar, wind, and hydropower are clean, sustainable, and abundant. They have a lower environmental impact and are increasingly cost-effective. By comparing the benefits of both nuclear and renewable energy, it is evident that the right energy mix is a more viable and sustainable option for the future.